2021
DOI: 10.13080/z-a.2021.108.014
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium leaching processes from sod-podzolic sandy loam reclaimed by increasing doses of finely ground dolomite

Abstract: The results of 8-variable column experiment on a strongly acidic sod-podzolic sandy loam reclaimed by the finely ground dolomite in a wide dose range are presented. The aim of the research was to measure and estimate leaching of magnesium (Mg) and its migration pattern. The dolomite powder at the different doses calculated by hydrolytic acidity (Hy) was applied at 225, 337.5, 450, 675, 900, 1350 and 1800 mg, that corresponded to 0.5, 0.75, 1.0, 1.5, 2.0, 3.0 and 4.0 Hy, respectively. The migratory ability of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Gransee and Führs (2013) reported that exchangeable Mg is readily mobile in the soil in comparison to other cations and is greatly influenced by the presence of Ca, K, and NH 4 . Being weakly bound to silicate clay minerals as well as SOM, soil solution Mg concentrations tend to be larger than that of other cations and increase with the addition of Ca 2+ and K + (Adomaitis et al., 2013; Litvinovich et al., 2021; Mikkelsen, 2011). The enhanced mobility of Mg in neutral to acidic soil, which characterizes the soils used in this study, tends to limit Mg retention (Yan & Hou, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gransee and Führs (2013) reported that exchangeable Mg is readily mobile in the soil in comparison to other cations and is greatly influenced by the presence of Ca, K, and NH 4 . Being weakly bound to silicate clay minerals as well as SOM, soil solution Mg concentrations tend to be larger than that of other cations and increase with the addition of Ca 2+ and K + (Adomaitis et al., 2013; Litvinovich et al., 2021; Mikkelsen, 2011). The enhanced mobility of Mg in neutral to acidic soil, which characterizes the soils used in this study, tends to limit Mg retention (Yan & Hou, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Ca is known to be a largely migratory element in water which is a function of Ca's large ionic radius that limits Ca from forming non‐exchangeable, Ca‐containing crystal lattices with other minerals, particularly under acidic soil conditions, such as those characterizing the soils used in this study (Table 1), thus rendering Ca to be highly leachable in humid environments with excess rainfall (Adomaitis et al., 2013; Litvinovich et al., 2021). Similar to the observations in this study, where leachate Ca had a generally inverse relationship with leachate NH 4 + , Adomaitis et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 10 years, negative changes in the quality of agricultural land are mainly caused by a significant reduction in the use of all types of fertilizers and liming (Polyakov et al, 2022). Extensive researches are devoted to various aspects of the liming of acidic soils (Danilov;Yakovleva;Nikolaeva, 2020;Islam et al, 2021;Kamprath;Smyth, 2005;Lavrishchev et al, 2020;Litvinovich et al, 2021aLitvinovich et al, , 2021bMohammed;Aman;Zewide, 2021;Nebolsin;Nebolsina, 2010;Opala, 2017). One of the problems of reclamation of acid soils is that most liming materials are quickly depleted in this soil due to leaching and fixation of cations (Lavrishchev et al, 2020;Rashid et al, 2021;Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Так, в Меньковском филиале АФИ создана многоуровневая система полевых экспериментов, которая служит методической базой для масштабных фундаментальных и прикладных исследований (60). Благодаря ей с использованием новых методических подходов были существенно развиты фундаментальные и прикладные основы точных систем удобрения посевов (61,62), методология фитосанитарного мониторинга и прикладные аспекты прецизионной интегрированной защиты растений (63,64), разработаны теоретические вопросы взаимодействия мелиорантов с почвой, исследованы адаптационные, агроэкологические и агроэкономические аспекты мелиорации и окультуривания дерново-подзолистых почв, в том числе на вторично осваиваемых сельскохозяйственных угодьях (60,62,65).…”
unclassified